2021
DOI: 10.14245/ns.2040458.229
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes Measurement Information System Physical Function Validation for Use in Anterior Cervical Discectomy and Fusion: A 2-Year Follow-up Study

Abstract: Objective: Our study aims to evaluate the correlation of Patient-Reported Outcomes Measurement Information System physical function (PROMIS PF) with legacy patient-reported outcome measures (PROMs) among patients undergoing anterior cervical discectomy and fusion (ACDF). Methods: A prospectively maintained database was retrospectively reviewed for ACDF surgeries performed between May 2015 and September 2017. Inclusion criteria were primary elective, single-or multilevel ACDFs for degenerative spinal pathology.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The adoption of more subjective, patient-centered metrics now serves as an adjunct to radiographic parameters, allowing a more encompassing assessment of patient satisfaction after spinal procedures. 30-32 Our study found that patients receiving ACDF or CDR at C5-C6 had similarly positive long-term PROMs for arm pain, neck pain, and physical function, highlighting the utility of both procedures for successful clinical outcomes. Specifically, the CDR patient cohort demonstrated improvement from preoperative baseline to the 1-year time point for all PROMs collected at all individual postoperative time points, with the exception of SF-12 PCS and PROMIS-PF at 6 weeks, and the ACDF patient cohort demonstrated improvement from preoperative baseline to the 1-year time point for all PROMs collected at all individual postoperative time points, with the exception of VAS arm at 1 year, NDI at 6 weeks and 1 year, and SF-12 PCS and PROMIS-PF at 6 weeks.…”
Section: Discussionmentioning
confidence: 66%
“…The adoption of more subjective, patient-centered metrics now serves as an adjunct to radiographic parameters, allowing a more encompassing assessment of patient satisfaction after spinal procedures. 30-32 Our study found that patients receiving ACDF or CDR at C5-C6 had similarly positive long-term PROMs for arm pain, neck pain, and physical function, highlighting the utility of both procedures for successful clinical outcomes. Specifically, the CDR patient cohort demonstrated improvement from preoperative baseline to the 1-year time point for all PROMs collected at all individual postoperative time points, with the exception of SF-12 PCS and PROMIS-PF at 6 weeks, and the ACDF patient cohort demonstrated improvement from preoperative baseline to the 1-year time point for all PROMs collected at all individual postoperative time points, with the exception of VAS arm at 1 year, NDI at 6 weeks and 1 year, and SF-12 PCS and PROMIS-PF at 6 weeks.…”
Section: Discussionmentioning
confidence: 66%
“…ACDF remains the gold standard for operative treatment of cervical degenerative pathology causing persistent neck and/or arm pain from nerve root compression with 137,000 procedures performed between 2006 and 2013 [ 7 ]. PROM questionnaires have been increasingly used by spinal surgeons to evaluate the postoperative quality-of-care and cost-effectiveness of this procedure [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…While a variety of physical function metrics exist in the spine literature, in this case, we chose to quantify physical function in terms of PROMIS PF scores due to their ease of administration and thorough validation in this population. 19 PROMIS PF specifically assesses factors such as mobility, dexterity, and ability to perform activities of daily living. 20 This relationship was further explored using linear regression to investigate the possible correlation between preoperative PROMIS score and either PROMIS or PHQ-9 postoperative scores.…”
Section: Discussionmentioning
confidence: 99%
“…Our study, however, adds to the current literature by contributing an investigation that has focused on the reverse directionality between physical function and depression, that is, how preoperative physical function affects depression. While a variety of physical function metrics exist in the spine literature, in this case, we chose to quantify physical function in terms of PROMIS PF scores due to their ease of administration and thorough validation in this population 19. PROMIS PF specifically assesses factors such as mobility, dexterity, and ability to perform activities of daily living 20.…”
Section: Discussionmentioning
confidence: 99%